Исследование влияния приёмов педагогики на уровень счастья на основе данных «Института Земли» Theearth institute - Кудрявцева, Н.В. (My University, 2016)
The problem of intercommunion of the level of intelligence and simple human happiness is examined in this article. During the reflection on this matter the data of the research center “Institute of the Earth”, the analytical conclusions of UNESCO are used. The author compares the system of education and bringing up with the level of happiness of some countries. As a result of undertaken study the author shows the basic elements of model of bringing up and education which allow a man to live a long healthy happy life.